Peranan Mediator dalam Penyelesaian Sengketa Kewarisan Perspektif Hukum Islam dan Hukum Positif - Nurhalisah Nurhalisah; Irfan Lewa (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab dan Hukum, 2021)
This thesis discusses the role of the mediator in the settlement of inheritance disputes with the perspective of Islamic law and positive law (Case Study No.1038 / Pdt.G / 2019 / PA.Mks at the Class 1A Makassar Religious Court). With mediation conducted by a mediator, it is likely that the parties to the dispute will be able to reconcile the parties in a dispute to a win-win solution and the peaceful dispute resolution process will be easier, faster, simpler, and less costly. This research was conducted by field research with descriptive analysis. With a normative juridical approach and a sociological (empirical) approach. The data sources in this study, namely: primary data, secondary data and searches of various literatures or references. Data collection methods used were observation, interviews, and documentation. Data processing and analysis techniques are carried out in three stages, namely: data identification, data reduction, and data editing. The results of this study indicate that the role of the mediator in the settlement of inheritance disputes at the Class 1A Makassar Religious Court has an important role in carrying out the mediation process based on the results of interviews with judges in court. It's just that the results / effectiveness achieved by the mediator in resolving inheritance disputes have not been effective because of the inhibiting factors for the mediator in resolving them, namely: 1) The parties in conflict have their emotions / egos not well controlled (lack of good faith from the disputing parties), 2) no one wants to budge, 3) the quality of the mediator. The implications of this research are: 1) with the mediation process carried out by a mediator in court, it is necessary that there is an increase in the process of settlement of cases, especially in mediation. The mediator must play an important role in carrying out the best dispute resolution so that the mediation process runs optimally and effectively, so that the parties are satisfied and no party feels disadvantaged, 2) this research is expected to have an impact on increasing the success of the mediator in mediating the parties litigating in Religious courts